Imaging of a serpentinite complex in the Kamuikotan Zone, northern Japan, from magnetotelluric soundings - Hiroshi Ichihara; Toru Mogi; Toshihiro Uchida; Hideyuki Satoh; Yusuke Yamaya; Masakazu Fujii; Shusaku Yamazaki; Kenji Okazaki; Noriko Tada (Earth, Planets and Space, 2021)
Abstract We conducted magnetotelluric measurements to investigate a large serpentinite complex in the northern Kamuikotan Zone that intruded a Cretaceous–Paleocene forearc sedimentary sequence. The resistivity model we derived by three-dimensional inversion clearly shows a low-resistivity zone beneath the outcrop of the serpentinite complex. We interpret the low-resistivity zone to represent aqueous pore fluid within a serpentinite mélange derived from the subducting Pacific plate or mantle wedge. Previous geological studies in the area have shown that the serpentinite mélange had uplifted during the early Pleistocene. They indicate that the ultramafic rocks and aqueous fluids have continued to rise in the area. The uplifting serpentinite body might have formed a zone enriched in pore fluid that promoted the occurrence of a previously identified intra-plate slow slip event. These results demonstrate the important role of fluid transport during tectonic processes related to uplift in subduction zones.